2021
DOI: 10.12998/wjcc.v9.i24.7163
|View full text |Cite
|
Sign up to set email alerts
|

Progressive disfiguring facial masses with pupillary axis obstruction from Morbihan syndrome: A case report

Abstract: BACKGROUND Morbihan syndrome is a rare illness, which presents with recurrent pitting edema on the upper two thirds of the face causing facial contour deformities, and Morbihan syndrome obstructing the pupillary axis with ptosis was seldomly reported. CASE SUMMARY A 59-year-old woman presented with a 15-year history of facial swelling that progressively invaded bilaterally from the inner canthus and eyelids outwards. Imaging examination indicated that the bilateral peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…However, this problem has not been the subject of publications so far. 10,11 Our patient, though almost the youngest among those being described, presented with all typical symptoms. Usually, the diagnosis of MS is made after the exclusion of other potential causes of swelling.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…However, this problem has not been the subject of publications so far. 10,11 Our patient, though almost the youngest among those being described, presented with all typical symptoms. Usually, the diagnosis of MS is made after the exclusion of other potential causes of swelling.…”
Section: Discussionmentioning
confidence: 61%
“…When seen in the acute setting, Morbihan syndrome can be from 5 months to 5 years, 6,9,[26][27][28] reaching in extreme cases up to 15 years. 10 As the disease is extremely rare, there are no randomized trials. It is suggested that the later treatment starts, the lower the chances of a full recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, early management is crucial for the well-being of the patient. Lack of awareness about MD progression from both the patient and physician, coupled with the absence of effective treatment, may contribute to the chronic progressive course of MD (13,30).…”
Section: Prognosis Of Morbihan Diseasementioning
confidence: 99%